2016
DOI: 10.1073/pnas.1610421113
|View full text |Cite
|
Sign up to set email alerts
|

2-Sulfonylpyrimidines: Mild alkylating agents with anticancer activity toward p53-compromised cells

Abstract: The tumor suppressor p53 has the most frequently mutated gene in human cancers. Many of p53’s oncogenic mutants are just destabilized and rapidly aggregate, and are targets for stabilization by drugs. We found certain 2-sulfonylpyrimidines, including one named PK11007, to be mild thiol alkylators with anticancer activity in several cell lines, especially those with mutationally compromised p53. PK11007 acted by two routes: p53 dependent and p53 independent. PK11007 stabilized p53 in vitro via selective alkylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 69 publications
(81 reference statements)
6
119
0
2
Order By: Relevance
“…Despite a large number of studies linking ERS to toxicants, currently, studies have yet to determine whether ERS is a contributing factor to busulfan-induced testicular damage and apoptosis [39, 40]. In this study, we demonstrated the relationship between testicular damage and ERS pathways in response to busulfan.…”
Section: Discussionmentioning
confidence: 67%
“…Despite a large number of studies linking ERS to toxicants, currently, studies have yet to determine whether ERS is a contributing factor to busulfan-induced testicular damage and apoptosis [39, 40]. In this study, we demonstrated the relationship between testicular damage and ERS pathways in response to busulfan.…”
Section: Discussionmentioning
confidence: 67%
“…However, there are now also emerging therapeutics targeting mutant p53. 21,22 There is an urgent need for novel therapies for TP53 mutant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There is not a simple explanation for several reasons, including that they may work simultaneously by multiple routes and that there are pleiotropic effects on mutating p53, including both loss and gain of function. An example of multiple routes is a small alkylator that covalently binds to mutant p53 in some cases, stabilizes it, and rescues its activity in some cancer cell lines, but kills other cancer cell lines via a reactive oxygen species (54). Similarly, several small molecules appear to reactivate p53 but, instead, cause cell death by other routes (3).…”
Section: Peptides and Peptide Combinations Selectively Kill Cancer Cementioning
confidence: 99%